ON EQUIVALENCE OF KELVIN AND MAXWELL MULTIELEMENT MODELS - Bogomolov, V.; Raznitsyn, I.; Богомолов, В. А.; Разницын, И. Л.; Богомолов, В. О.; Разніцин, І. Л. (Харьковский национальный автомобильно-дорожный университет, 2015)
The problem of Kelvin and Maxwell model equivalence in one- and three-dimensional cases is investigated. The equations of one model transfer to the other one have been given.
ОБ ЭКВИВАЛЕНТНОСТИ МНОГОЭЛЕМЕНТНЫХ МОДЕЛЕЙ КЕЛЬВИНА И МАКСВЕЛЛА
ПРО ЕКВІВАЛЕНТНІСТЬ БАГАТОЕЛЕМЕНТНИХ МОДЕЛЕЙ КЕЛЬВІНА ТА МАКСВЕЛЛА
Keywords: linear viscoelasticity; Kelvin model; Maxwell model; equivalent models; линейная вязкоупругость; модель Кельвина; модель Максвелла; эквивалентные модели; лінійна в’язкопружність; модель Кельвіна; модель Максвелла; еквівалентні моделі; 656.015